Information on yield and other advantages of sorghum (Shi gnouma de bè senekela ka sôrôkofô) - International Institute of Tropical Agriculture (International Livestock Research Institute, 2018)
Episode two of a radio program series by the Africa RISING program in Bambara dialect that is spoken in southern Mali. In this episode which aired on KAFO KAN radio on 27 October 2017, farmers are being provided with relevant information about the yield advantages offered by dual-purpose sorghum over other varieties commonly grown in Bougouni. This radio program was produced as part of Africa RISING activity – Use of Interactive radio to scale-up agriculture and nutrition technologies in Africa RISING Mali.